Enantioselective 1,1-Arylborylation of Alkenes: Merging Chiral Anion Phase Transfer with Pd Catalysis - Nelson, Hosea M. (J Am Chem Soc, 2015)
A palladium-catalyzed three-component coupling of α-olefins, aryldiazonium salts, and bis-(pinacolato)diboron affords direct access to chiral benzylic boronic esters. This process is rendered highly enantioselective using an unprecedented example of cooperative chiral anion phase transfer and transition-metal catalysis.